(3eONd GSJQGJjLj eJcGed hYUQjs - (3eCehf fOje(B, (3YcQhTs ((3YeGf(B:s (3OGQ hGFd(B,s, 2004)
(3eONd GSJQGJjLj eJcGed, GdJNWjW GdGSJQGJjLj ddefJLGJ GdLOjOI, GSJQGJjLjI GdefJLGJ GdLOjOI, YedjI JWhjQ efJLGJ LOjOI, Ndb hJWhjQ eaghe GdefJL GdLOjO, JWhjQ GdefJLGJ GdLOjOI, GSJQGJjLjGJ JShjb GdefJLGJ GdLOjOI, WQM hGOGQI GdefJLGJ GdLOjOI aj GdShb, GOGQI YedjI WQM GdefJL GdLOjO aj GdShb(B.s
(3GdeQGLY U(B.481s
Keywords: (3EOGQI GdJShjbs; (3GdJNWjWs; (3GdJShjbs